2021
DOI: 10.1016/j.heliyon.2021.e08219
|View full text |Cite
|
Sign up to set email alerts
|

Climate change/global warming/climate emergency versus general climate research: comparative bibliometric trends of publications

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 88 publications
(129 reference statements)
0
21
0
1
Order By: Relevance
“…This bibliometric study's protocol ( Fig. 1 ) was similar to another study on comparative bibliometric trends of publications in two different topics (climate and climate change); 30 this protocol is divided into five steps, which are detailed below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bibliometric study's protocol ( Fig. 1 ) was similar to another study on comparative bibliometric trends of publications in two different topics (climate and climate change); 30 this protocol is divided into five steps, which are detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…The publication ratios were calculated by dividing the number of publications in a category in one record by the number of publications in another record, allowing us to distinguish and contrast MPs research from PFAS research. Santos and Bakhshoodeh (2021) pioneered this method by comparing trends in climate change/global warming/climate emergency research to general climate research 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Long before human existence and activities, the earth has gone through different fluctuations of cooling and warming in the past. The major natural factors that share to climate change include sun’s intensity, natural GHGs concentrations, volcanic eruptions, orbital changes, movement of crustal plates, El Nino-Southern Oscillation (ENSO; Thompson, 2010 ; Rosso Grossman, 2018 ; Santos and Bakhshoodeh, 2021 ). However, the projections and analyses have shown that earth warming primarily occurred since the last century is happening at rapid speed which cannot be interpretated only by natural causes.…”
Section: General Background and Climate Change Statusmentioning
confidence: 99%
“…The mitigation of climate change is a technical measure that aims to limit and/or prevent anthropogenic greenhouse gas emissions. Technologies for climate change mitigation are classified into: (i) conventional mitigation, which employs efforts to reduce the utilization of fossil fuels, including the use of RESs and efficiency gains, and (ii) CO 2 removal technology, which directly targets the original reason of climate change by sequestering CO 2 from the air [57]. In comparison with the single conventional generation system, the HES has positive effects on the environment.…”
Section: Environmental Analysismentioning
confidence: 99%